Changes in pain perception during pregnancy after one-time maximal physical exertion and an 8-week high-intensity interval training - Leźnicka, Katarzyna; Gasiorowska, Agata; Pawlak, Maciej; Jażdżewska, Aleksandra; Maciejewska-Skrendo, Agnieszka; Chudecka, Monika; Szumilewicz, Anna (Frontiers in Physiology, 2023)
Physical activity during pregnancy is considered a necessary prerequisite for the proper progression of pregnancy and postpartum. even relatively low levels of physical exertion can alter the perceived threshold for painful and nonpainful stimuli, including labor pain. Studies that record changes in pain perception during pregnancy as influenced by physical exercise are sparse. They mainly concern the effects of exercise on fear of childbirth in women attending traditional childbirth classes or pain tolerance in women with and without fear of childbirth. Our research is groundbreaking. For the first time, pregnant women participated in an 8-week HIIT (high-intensity interval training) exercise program. The aim of our project was to determine the effects of physical activity (including controlled physical training prepared according to the latest guidelines for physical activity in pregnancy) on pain perception and pain sensitivity. As a result of the physical training, the pain tolerance in pregnant women increased, even though their subjective pain sensitivity did not change